GENERATION Z CONSUMPTIVE ONLINE BEHAVIOR PATTERNS BASED ON CONSUMPTION THEORY IN AN ISLAMIC ECONOMIC PERSPECTIVE - Pradanimas, Aqilla; Masyhuri, Masyhuri; Julaihah, Umi (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
This research delves into the online consumptive behaviour of Generation Z in Parangjoro Village, exploring it through the lens of Islamic economics. While Islamic teachings emphasize the importance of adhering to ethical consumption practices, the study reveals that the online shopping habits of Generation Z in Parangjoro are not fully aligned with these principles. The inclination to purchase based on desires rather than needs, coupled with a lack of consideration for product quality, underscores the existing gap between Islamic teachings and consumer practices. Factors such as convenience, affordability, and a wide array of choices in online stores significantly influence their behaviour. The impact of this consumptive behaviour manifests in social envy, financial strain, and a diminishing interest in savings. This conclusion highlights the urgency of addressing this misalignment by promoting Islamic economic education, awareness campaigns on mindful consumption, financial management training, and active involvement of parents and society in guiding Generation Z towards more conscientious and Islamically-aligned consumption practices. The findings contribute to the ongoing discourse on harmonizing contemporary consumer behaviour with the principles of Islamic economics.